The Present and Future of the Chinese Surveying and Charting - Gui, Liu Chang (The International Hydrographic Review, 2015)
The ocean covers more than seventy per cent of the total area of the earth, so its political, economical and military values have attracted great human attention since early time. Along with the development of ocean related activities in the recent twenty to thirty years, oceanic economics have become an important factor for countries concerned with the sea. Many countries in the world specify ocean study as one of the important scientific research areas and at the same time pay more and more attention to ocean surveying and charting. As a result, the science and technology of ocean surveying and charting developed rapidly in these countries. That is true for China, where science and technology in this respect developed continuously. Here is a brief description of China’s main status on ocean surveying and charting and also some ideas about future development in these areas.